Kedah development action plan 1991-2000 evaluation & achievement - Ibrahim, Fatimah Wati (Universiti Utara Malaysia Press, 2006)
Written for policy makers, academic researchers, students, economists and the general public, Kedah Development Action Plan 1991-2000: Evaluation and Achievement presents a comprehensive exposition of the issues involved in the economic development of the state.It evaluates the achievements of the state’s developmental efforts in accelerating the socio-economic progress of the state of Kedah Darul Aman.This book aims to improve the readers’ understanding about economic issues by focusing on simple analysis of the economic environment of the state.This book provides analyses of the main sectors of economic development that the state gives priority to, which include, sectoral performance, industrial sector, tourism sector, agricultural sector, and human resource development.The Development of Bumiputra Commercial and Industrial Community, poverty eradication in complete.Each chapter discusses sector-specific issues, challenges and constraints; and opportunities in the priority areas.The analyses in this book provide a broad perspective on the role of the state government in the economy.It highlights issues pertaining to resource allocation, income, distribution, economic development and human resource.